PENGARUH HIPNOTERAPI TERHADAP PENURUNAN SKALA NYERI DISMENORE. - Ari Kurniyanti Mizam (LPPMK STIKES Widyagama Husada, 2020)
Dysmenorrhea is pain during menstruation. Symptoms of dysmenorrhea are very typical, namely complaints of abdominal pain or stomach cramps. The management of primary dysmenorrhea pain can be done by non pharmacological. One of the non-pharmacological relaxation techniques is hypnotherapy because hypnotherapy techniques can produce a sense of comfort and can produce endorphin hormones that can suppress pain. Aim : Knowing the effect of hypnotherapy on reducing the primary dysmenorrhea pain scale based on literature studies in the last 6 years.Method :The method used in this literature study is to obtain articles from the search results of scientific research articles from the 2014-2020 period using the Taylor & Francis Group, Sienta, DOAJ, Research Gate, and Google Shcolar data base. As many as 120 articles were obtained which were then carried out by the identification and screening process, so that 10 articles were obtained that match the inclusion criteria, with a pre-experimental research design of 5 articles and a quasi-experimental study of 5 articles. Result: The test results of these journals which state that the p value <0.05 is defined as a significant difference between before the intervention was given and after the intervention was given.Conclusion: The conclusion from this literature review is that there is an effect of hypnotherapy on reducing the pain scale of primary dysmenorrhea. Suggestions for nursing students and nurses, to improve the science of hypnotherapy as part of complementary therapy to overcome dysmenorrhea pain problems. Bibliography : 36 literature (2010-2020) Keywords : hypnotherapy, primary, dysmenorrhea